Intellectual disability, personality disorder and offending: a systematic review. Issue 2 (2nd March 2015) - Rayner, Kelly; Wood, Harry; Beail, Nigel; Nagra, Maninder Kaur
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This review seeks to systematically review studies where personality disorder has been explored as a descriptive or possible predictive factor in offending behaviour in people with an intellectual disability. The papar aims to discuss this issue. Design/methodology/approach – A systematic search of several databases was conducted and 15 studies met the inclusion criteria and were included in this review. Findings – Methodological limitations and problems in accurate diagnosis within this client group preclude firm conclusions being reached. Originality/value – It is concluded that further research should be conducted, with particular attention paid to the conceptualisation and assessment of personality disorder.